2006
DOI: 10.1093/rpd/ncm151
|View full text |Cite
|
Sign up to set email alerts
|

A methodology for auto-monitoring of internal contamination by 131I in nuclear medicine workers

Abstract: The manipulation of 131I in Nuclear Medicine involves significant risks of internal contamination of the staff. In the event of an accidental contamination, or when the Radiological Protection Program includes routine individual monitoring of internal contamination, it is necessary to implement internal dose estimation through in vivo and in vitro bioassay techniques. Due to the huge extension of the Brazilian country, this type of monitoring becomes unfeasible if all measurements have to be performed at the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 2 publications
0
4
0
2
Order By: Relevance
“…Compared with the external individual monitoring, the method of internal individual monitoring is diversified, and the result is easily influenced by many factors. The published literature reports [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ] regarding internal exposure in the field of nuclear medicine mainly did research on commonly used nuclides 131 I, 99m Tc and 18 F, and among them, internal exposure induced by 131 I were most studied and reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the external individual monitoring, the method of internal individual monitoring is diversified, and the result is easily influenced by many factors. The published literature reports [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ] regarding internal exposure in the field of nuclear medicine mainly did research on commonly used nuclides 131 I, 99m Tc and 18 F, and among them, internal exposure induced by 131 I were most studied and reported.…”
Section: Discussionmentioning
confidence: 99%
“…Research in this area is divided into two parts: the first part is the study of the committed effective dose resulting from intake of radionuclides. A series of studies have been carried out on the internal exposure of nuclear medical staff by air sampling [ 9 , 10 , 11 , 12 , 13 ], direct measurement [ 14 , 15 , 16 , 17 , 18 ] or biological materials sample analysis [ 17 , 19 , 20 ]. The second part is the study of the necessity of internal monitoring for nuclear medicine staff.…”
Section: Introductionmentioning
confidence: 99%
“…A comparative approach based on the exposure scenarios and safety conditions adopted in this work indicates that the use of 131 I presents the higher risk of intake by workers. However, due to costs associated with transporting workers or bioassay samples to laboratories for analysis, it is suggested that the nuclear medicine centers use their own diagnostic devices to perform the monitoring of the workers Vidal, 2007;. Since the occupationally exposed group with higher risk of intake are most likely professionals who work in the radiopharmacy laboratories of the nuclear medicine centers (Freitas, 1991), they should be the first group evaluated for implementing an internal monitoring plan.…”
Section: Discussionmentioning
confidence: 99%
“…Diversos trabalhos desenvolvidos na Suíça [9,10,11], Brasil [12,13,14] e Polônia [15] levaram a cabo pesquisas de medições realizadas nos SMN, usando instrumentos de laboratório comumente disponíveis e que, portanto, não requerem equipamentos complexos e caros para análises quantitativas precisas, como contadores de corpo inteiro.…”
Section: Introductionunclassified